ELECTRONIC STRUCTURES OF DIRECT-STACKED BIPHENYLENE NETWORK: A DFT STUDY - Art Anthony Z. Munio; Alvanh Alem G. Pido; Kenneth Ian M. Balili (International Engineering Journal For Research & Development, 2022)
Here we provide a short theoretical report on the electronic structures of direct-stacked Biphenylene networks using density functional theory. The calculations reveal that direct-stacking of Biphenylene networks leads to splitting and shifting of the electronic bands, which leads to the slight deviation of the electronic density of states of the direct-stacked Biphenylene network compared to the monolayer Biphenylene network. However, in general, the band structure and density states of the direct-stacked systems resemble that of the monolayer Biphenylene network The calculations on the charge density difference show a very small charge redistribution in the direct-stacked systems. These findings provide a preliminary understanding of the properties Biphenylene network in its stacked form.